2012
DOI: 10.1371/journal.pone.0053049
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection in the Chromosome 16 VKORC1 Genomic Region Has Contributed to the Variability of Anticoagulant Response in Humans

Abstract: VKORC1 (vitamin K epoxide reductase complex subunit 1, 16p11.2) is the main genetic determinant of human response to oral anticoagulants of antivitamin K type (AVK). This gene was recently suggested to be a putative target of positive selection in East Asian populations. In this study, we genotyped the HGDP-CEPH Panel for six VKORC1 SNPs and downloaded chromosome 16 genotypes from the HGDP-CEPH database in order to characterize the geographic distribution of footprints of positive selection within and around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…The absolute pairwise LD among rs2359612, rs8050894, rs9934438, rs9923231 and rs7196161 in East Asian populations is not an unusual finding. In fact, a 505 kb region of strong LD, which contains VKORC1 and 24 neighboring genes, is located on chromosome16 only in East Asian populations and this genomic region may have been submitted to a near complete selective sweep in all East Asian populations and only in this geographic area [61].…”
Section: Drug-response Related Snps With High Mafs In Individual Popumentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute pairwise LD among rs2359612, rs8050894, rs9934438, rs9923231 and rs7196161 in East Asian populations is not an unusual finding. In fact, a 505 kb region of strong LD, which contains VKORC1 and 24 neighboring genes, is located on chromosome16 only in East Asian populations and this genomic region may have been submitted to a near complete selective sweep in all East Asian populations and only in this geographic area [61].…”
Section: Drug-response Related Snps With High Mafs In Individual Popumentioning
confidence: 99%
“…There is evidence of natural selection for some of these SNPs, while the others require further investigations. For example, among the SNPs with MAFs � 0.8 in at least one super-or subpopulation the possibility of natural selection has been suggested for rs776746 [111], rs2740574 [111], rs2359612 [61], rs8050894 [61], rs9934438 [61], rs9923231 [61], rs1346268 [112], rs7294 [61]. Hence, the pattern of allele frequency distribution observed for these 159 drug response-related SNPs may not be observed for any random 159 SNPs.…”
Section: Human Evolution and Geographic Distribution Of The Drug-respmentioning
confidence: 99%
“…It is clear that warfarin dosing incorporates with the CYP2C9*2 and VKORC11639G>A single nucleotide polymorphisms, but do not adequately explain the variability in warfarin dosing in African populations 14 Studies on haplotypes of VKORC1 gene showed that the highest haplotype diversity was observed in SubSaharan Africans. The -1639 A allele (rs9923231) carried by haplotype H1, is the most frequent VKORC1 haplotype worldwide (49.7%) 15 . Data on prevalence of VKORC11639G>A SNP among Sudanese populations are incomplete, but the available information concluded to that this SNP is the most frequent SNP among Sudanese, Kenyans and Egyptians but not in West Africans.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of vitamin K recycling depends on a polymorphism in the promoter region of the vitamin K epoxide reductase complex subunit 1 (VKORC1) gene [13] . In East Asia, positive selection for an allele that is associated with low vitamin K recycling rates started around 4,500 years ago [14] . Allele frequency of this derived −1639A VKORC1 allele is around 75–100% in East Asians, whereas it is below 10% in Africans and intermediate in Europeans [15] .…”
Section: Vitamin K Epoxide Reductase Complex Subunit 1 Polymorphismmentioning
confidence: 99%
“…Allele frequency of this derived −1639A VKORC1 allele is around 75–100% in East Asians, whereas it is below 10% in Africans and intermediate in Europeans [15] . The near complete selective sweep in East Asian populations is remarkable due to the recent and rapid occurrence, and strongly suggests a survival benefit rather than the loss of redundant function [14] . However, it is an enigma why a polymorphism associated with reduced vitamin K recycling would carry a significant survival benefit, given that even high-dose vitamin K intake is not associated with adverse side effects [16] .…”
Section: Vitamin K Epoxide Reductase Complex Subunit 1 Polymorphismmentioning
confidence: 99%